Transforming Education with the "Merdeka Belajar Curriculum: Digging into Challenges and Crafting Effective Strategies in Rural Indonesia - Pratiwi, Widya Rizky (ENGLISH FRANCA : Academic Journal of English Language and Education, 2025)
The Merdeka Belajar curriculum has been widely recognized for its flexibility, student-centered approach, and potential to enhance digital literacy. However, limited studies have explored its specific impact on English language teaching (ELT), particularly in rural secondary schools. This study investigates the practice of the Merdeka Belajar curriculum in ELT at SMP Negeri 5 Sangatta Utara, focusing on the barriers encountered by teachers and students and the strategies employed to address them. Using a descriptive qualitative approach, data were collected using semi-structured interviews, observations, and document analysis. The study involved three English teachers and ten seventh-grade students. Data were analyzed using Miles and Huberman’s framework, which includes data condensation, data display, and conclusion verification. The findings reveal that while the Merdeka Belajar curriculum encourages innovative teaching methods and student engagement, its implementation in rural settings is hindered by inadequate resources, limited technological infrastructure, and teachers’ readiness. To overcome these challenges, teachers employed adaptive strategies such as contextualized lesson planning, multimodal teaching techniques, and collaborative learning approaches. These strategies helped optimize the curriculum’s objectives despite existing limitations. The study provides valuable insights for educators and policymakers on how to enhance curriculum implementation in resource-constrained environments. It underscores the need for targeted professional development programs, improved educational infrastructure, and community involvement to maximize the curriculum’s impact on English language learning in rural Indonesia.